2019
DOI: 10.1080/02670844.2019.1660035
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of compositionally modulated nanocrystalline Ni–W coatings

Abstract: The present study deals with corrosion behaviour of compositionally modulated nanocrystalline Ni-W alloy coatings and conventional hard chrome coatings. Compositionally modulated Ni-W alloy coatings of known composition were systematically deposited using pulse current deposition. The corrosion behaviour was analysed using potentiodynamic polarization and impedance spectroscopy in 2N H 2 SO 4 . Compositionally modulated Ni-W alloy coatings depicted substantial improvement in corrosion resistance over its singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Corrosion resistance properties results are given in Tables 5 and 6, and it can be observed that the incorporation of epoxy resin and acrylic grafting polymers helped to develop a coating with improved salt spray resistance and humidity. The corrosion resistance properties of the developed coating were optimised with the increase of epoxy content in the coatings [15,[24][25][26][27][28].…”
Section: Corrosion Resistance Properties Of Acrylic Cathodic Electrod...mentioning
confidence: 99%
“…Corrosion resistance properties results are given in Tables 5 and 6, and it can be observed that the incorporation of epoxy resin and acrylic grafting polymers helped to develop a coating with improved salt spray resistance and humidity. The corrosion resistance properties of the developed coating were optimised with the increase of epoxy content in the coatings [15,[24][25][26][27][28].…”
Section: Corrosion Resistance Properties Of Acrylic Cathodic Electrod...mentioning
confidence: 99%
“…Excessive internal stress can cause bending of the substrate or cracking of the coating, or even falling off, thus affecting the corrosion resistance and mechanical properties of the coating [15]. The internal stress of the coating is divided into compressive stress and tensile stress [16][17][18]. The coating generates compressive stress during the electrodeposition reaction due to the difference between the thermal expansion coefficients of the substrate and the coating [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Eskin [6] showed that the corrosion resistance of Co-W plating coating is comparable or even better than conventional Cr plating but the wear resistance is lower. Wasekar [7] proposed that the compositionally modulated Ni-W alloy coatings also depicts substantial improvement in corrosion resistance over hard chrome coating. However, its hardness and wear resistance is unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%